2019
DOI: 10.1073/pnas.1900176116
|View full text |Cite
|
Sign up to set email alerts
|

CarD contributes to diverse gene expression outcomes throughout the genome of Mycobacterium tuberculosis

Abstract: The ability to regulate gene expression through transcription initiation underlies the adaptability and survival of all bacteria. Recent work has revealed that the transcription machinery in many bacteria diverges from the paradigm that has been established in Escherichia coli. Mycobacterium tuberculosis (Mtb) encodes the RNA polymerase (RNAP)-binding protein CarD, which is absent in E. coli but is required to form stable RNAP-promoter open complexes (RPo) and is essential for viability in Mtb. The stabilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 49 publications
9
48
0
Order By: Relevance
“…It localizes to promoter regions where the housekeeping sigma factor resides, directly binds to the RNAP β subunit, stabilizes the open promoter complex, and is required for transcription from rRNA promoters [2,3,5]. Recent work in Mycobacterium tuberculosis using mutants of CarD (the CdnL homolog) unable to bind either RNAP or DNA showed that CdnL can act as an activator or repressor of transcription depending on the stability of the RNAP-promoter complex [7]. M. tuberculosis CarD is essential for growth in culture, persistence in mice, and survival during genotoxic stress and starvation [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…It localizes to promoter regions where the housekeeping sigma factor resides, directly binds to the RNAP β subunit, stabilizes the open promoter complex, and is required for transcription from rRNA promoters [2,3,5]. Recent work in Mycobacterium tuberculosis using mutants of CarD (the CdnL homolog) unable to bind either RNAP or DNA showed that CdnL can act as an activator or repressor of transcription depending on the stability of the RNAP-promoter complex [7]. M. tuberculosis CarD is essential for growth in culture, persistence in mice, and survival during genotoxic stress and starvation [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Such a www.nature.com/scientificreports www.nature.com/scientificreports/ severe reduction in rRNA operon expression would impact protein synthesis leading to downstream deleterious consequences seen in GreA depleted cell. Previous studies showed that the expression of rRNA in mycobacteria is positively regulated by CarD 28,36 . In GreA_CKD, apart from the reduction in rRNA expression, the expression of CarD was also reduced (Earlier section, Figs.…”
Section: Resultsmentioning
confidence: 98%
“…When CarD was discovered, it was found to be a negative regulator as its depletion led to upregulation of 16 S rRNA 27 . However, in a subsequent study, it was shown to be a global regulator of transcription initiation 28,36 . Trancript analysis of CarD depleated M.smegmatis showed differential regulation of large number of genes including rRNA and translational machinary genes 27 .…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, special transcription regulators are needed to support mycobacterial growth and gene regulatory networks are very complicated. For example, the transcription factors CarD and RbpA which are absent in E. coli perform essential roles for mycobacterial growth by stabilizing RPo [21,22], and interaction between RbpA and SigB regulates PPK1 transcription in mycobacteria [23]. The speci city of Mtsp17 probably adapts to the unstable mycobacterial RPo.…”
Section: Discussionmentioning
confidence: 99%